Effects of waste disposal on soil and water chemistry at an industrial complex near Somerset West, South Africa - Doel, Sean Laurens (Department of Geological Sciences, 2023)
The estimated total annual production of waste in South Africa is 318 million metric tons. Of this waste, 3.8%, approximately 12 million metric tons, arises from the chemical manufacturing industry. Although increasing attention is being given to methods of land treatment for waste disposal waste is still disposed of by dumping/stockpiling. This study focuses on the effects of such waste disposal on soil and water chemistry at an industrial complex near Somerset West, South Africa. Since 1903 a multitude of industrial activities have occurred on the site including manufacture of explosives, chemicals, fertilizers and vinyl coated products: Decommissioning of the industrial complex is presently in progress. The overall objective of this study was to conduct an investigation of the water and soils in an area termed the Dead Tree Area. The area was considered of particular interest due to the presence of a sulphur stockpile, gypsum waste dumps and fertilizer wastewater evaporation site located immediately adjacent to the area. Four key objectives were addressed in the study, namely: (i) to chemically characterise the water and soils in the Dead Tree Area, (ii) to assess the degree of contamination of the water and soils in the area, (iii) to question whether tree mortality in the area could have resulted from toxicy or deficiency effects, and (iv) to determine the potential of gypsum application as a means of remediating dispersed, sodic soils.